Epidemiology of fractures in Children at College of Medical Sciences and Teaching Hospital, Bharatpur, Nepal - Gupta, HK (Journal of College of Medical Sciences-Nepal, 2015)
Objective To study the epidemiology of fractures in the pediatric population. Methods All the cases of fractures of age 14 yrs or less presenting in emergency room or outdoor patient department of Orthopaedics during the time period of January 2013 to December 2013 were included in the study and prospectively studied. Demographic data were collected and analysed by descriptive methods. Results The incidence of fracture was more in male child. Most fractures occurred in age group of 6 to 14 years. Lower limb fractures (56.8%) were more common than upper limb fractures. Incidence of injuries was more during summer most common mode of trauma being motor vehicle accidents (26%). Conclusion Proper supervision and guidance during outdoor activities, on the play ground and proper home safety measures with improved road conditions and proper traffic knowledge can markedly reduce the incidence of pediatric trauma. DOI: http://dx.doi.org/10.3126/jcmsn.v10i1.12760 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(1); 1-4